2010
DOI: 10.1007/s10555-010-9213-8
|View full text |Cite
|
Sign up to set email alerts
|

p66Shc—a longevity redox protein in human prostate cancer progression and metastasis

Abstract: Abstractp66Shc, a 66 kDa proto-oncogene Src homologous-collagen homologue (Shc) adaptor protein, is classically known in mediating receptor tyrosine kinase signaling and recently identified as a sensor to oxidative stress-induced apoptosis and as a longevity protein in mammals. The expression of p66Shc is decreased in mice and increased in human fibroblasts upon aging and in aging-related diseases, including prostate cancer. p66Shc protein level correlates with the proliferation of several carcinoma cells and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 143 publications
(212 reference statements)
2
69
0
Order By: Relevance
“…The protein level of p66Shc, a 66 kDa Src homologous-collagen homologue (Shc), is involved in regulating the proliferation of several carcinoma cells including PCa cells and can be up-regulated by steroids [20-23]. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein level of p66Shc, a 66 kDa Src homologous-collagen homologue (Shc), is involved in regulating the proliferation of several carcinoma cells including PCa cells and can be up-regulated by steroids [20-23]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, by inhibiting AR signaling, AMD and DME may prevent the interaction of AR with p85α regulatory subunit of PI3K; which results in decreased Akt activation [39]. p66Shc, a 66 kDa oxidase, can up-regulate cell growth and is elevated in steroid-regulated carcinomas [20,23,40]. In PCa, p66Shc plays a role in mediating the cross-talk signal between steroids and tyrosine phosphorylation [40], which is involved in regulating cell proliferation and apoptosis [22,23,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that one of the isoforms of SHC1 (p66 Shc ) can enhance proliferation of prostate cancer cells [40] and high expression of p66 Shc was found in primary breast tumors with high metastatic potential [41]. It also mediates steroid actin by regulating oxidative stress-induced apoptosis [42]. All the information suggests that SHC1 is a potential prognostic marker and cancer treatment target.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, p66ShcA was shown to antagonize ERK activation via negative regulation of c-fos promoter activity (52) and to be mainly involved in oxidative stress signaling (53). Additionally, the role of p66ShcA in tumor metastasis is controversial (54,55). Therefore, the reduction of the p-ERK level after ShcA knockdown with the pan-ShcA siRNA was likely due to the depletion of p52/46ShcA.…”
Section: Discussionmentioning
confidence: 99%